619 Evaluating the effectiveness of targeted ADC therapy in a patient-derived ex vivo tumoroid model, 3D-EX, for quantitative tumor cell killing. (9th November 2020) - Kreahling, Jenny; Ehrhart, Jared; Pabon, Mibel; Iwanowycz, Stephen; Pastoor, Tina; Altiok, Soner
Abstract : Background: Antibody drug conjugates (ADCs) are an effective tool for site directed delivery of cytotoxic agents to cancer cells. Tailoring of ADC-specificity to the uniqueness of a patient's tumor can aid in direct-targeting of tumor cells and potentially improve drug responsiveness. Here we evaluate the potential of using an ADC therapy for targeted tumor cell death and immune cell activation in combination with checkpoint inhibitors in 3D tumoroids. Methods: All human tumor samples were obtained with proper patient consent and IRB approval. Fresh patient tumor tissue of various histologic types including CRC and NSCLC were processed to generate uniform sized live 3D tumoroids measuring 150 µm in size. Treatment groups included a conjugated ADC therapeutic antibody alone or in combination with PD-1/PD-L1 inhibitors. Culture supernatants were collected for multiplex analysis of cytokine release in media. Additionally, flow cytometry was used to assess the activation profile of resident immune cells in combination with high-content confocal imaging to determine extent of tumor cell death in the intact tumor extracellular matrix. Results: Using fresh patient-derived tumoroids, we observed ADC-mediated cell death and activation of immune cells within the tumor microenvironment. Production of pro-inflammatory cytokines correlated with increased activation of tumor infiltrating immune cell populations. The improved immune response led to increased tumor cell killing within the 3D tumor microenvironment observed by high-content confocal imaging. Conclusions: In this study we demonstrate that our physiologically relevant 3D tumoroid model is an effective system to assess novel antibody drug conjugates and to develop rational drug combinations with other immuno-oncology agents. Furthermore, implementation of 3D-EX platform, in the clinical setting, may also allow for determination of the most effective combinatorial immuno-oncology treatment strategies for individualized patient care. Ethics Approval: The study was approved by Chesapeake IRB Pro00014313.